The impact of interface states on the mobility and drive current of In0.53Ga0.47As semiconductor n-MOSFETs. (June 2015) - Osgnach, Patrik; Caruso, Enrico; Lizzit, Daniel; Palestri, Pierpaolo; Esseni, David; Selmi, Luca
Abstract: Accurate Schrödinger-Poisson and Multi-Subband Monte Carlo simulations are used to investigate the effect of interface states at the channel-insulator interface of In 0.53 Ga 0.47 As MOSFETs. Acceptor states with energy inside the conduction band of the semiconductor can explain the dramatic Fermi level pinning observed in the experiments. Our results show that these states significantly impact the electrical mobility measurements but they appear to have a limited influence on the static current drive of short channel devices.